2022
DOI: 10.1186/s12887-022-03136-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of advance exposure to an animated surgery-related picture book on preoperative anxiety and anesthesia induction in preschool children: a randomized controlled trial

Abstract: Background Our aim was to investigate whether early surgical preparation by reading an animated picture book about procedure-related events could reduce the preoperative anxiety in preschoolers. Methods 131 patients, aged 3–6 years and underwent elective minor surgery were randomized either to a control or a picture book group. Both groups received general information about surgery and anesthesia in pre-anesthesia clinic. Patients in study group al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Distraction as a preoperative anxiety management technique has positive effects on paediatric patients undergoing elective surgery (Wu et al, 2022). This finding is in line with the results of previous research, including that of Aydın and Uyar (2021) and of Yang et al (2022), who showed that reading an animated picture book ( Tom in the Hospital ) at home 1 week before surgery reduced the level of preoperative anxiety in preschool children. Macindo et al (2015) determined that a 3D storybook alleviated preoperative anxiety, while Sekhavatpour et al (2019) found that reading animated picture books was effective in reducing postoperative anxiety in children.…”
Section: Discussionsupporting
confidence: 92%
“…Distraction as a preoperative anxiety management technique has positive effects on paediatric patients undergoing elective surgery (Wu et al, 2022). This finding is in line with the results of previous research, including that of Aydın and Uyar (2021) and of Yang et al (2022), who showed that reading an animated picture book ( Tom in the Hospital ) at home 1 week before surgery reduced the level of preoperative anxiety in preschool children. Macindo et al (2015) determined that a 3D storybook alleviated preoperative anxiety, while Sekhavatpour et al (2019) found that reading animated picture books was effective in reducing postoperative anxiety in children.…”
Section: Discussionsupporting
confidence: 92%
“…According to the results of several existing studies in the literature and a preliminary study in our center [ 1 ], the mean mYPAS-SF score at T3 was approximately 60 ± 18 in the control group. With a two-sided significance level of 5% and an efficacy of 80%, 36 participants per group were required to detect a 20% decrease between the intervention and control groups (12 on the rating scale).…”
Section: Sample Size Estimationmentioning
confidence: 97%
“…Preoperative anxiety in pediatric patients usually begins at admission when they know that they would undergo a surgical operation [ 1 ]. Up to 50–60% of children undergoing surgical procedures experience significant preoperative anxiety [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar study was performed in which a group of preschoolaged children were given animated surgery-related picture books one week before surgery versus a control group. The study revealed that preschool-aged children had decreased pre-operative anxiety when given an animated picture book explaining their upcoming surgery compared to those who did not receive an animated picture book [5]. Lastly, meditation effects on anxiety were examined in adolescents.…”
Section: Visualization and Meditation Interventionsmentioning
confidence: 99%